Cutting-Edge Approaches in Urinary Incontinence Treatment: A Comprehensive Review - Winiarek, Karolina; Michalska, Martyna; Wardyn, Wiktor; Guzowski, Cezary; Murawska, Joanna; Ziemińska, Daria; Burczyk, Rafał; Kędziora-Kornatowska , Kornelia (Quality in Sport, 2024)
Introduction: Urinary incontinence is a prevalent health issue that profoundly impacts the quality of life for patients worldwide. Traditional treatments, including pharmacotherapy and surgical procedures, often fall short, leaving many individuals struggling with bladder control issues that restrict physical and social activities and cause significant psychological distress. Recent advancements in therapeutic methods—encompassing behavioral therapies, cutting-edge medical technologies, innovative pharmacotherapy, and advanced surgical techniques—offer promising alternatives. By exploring the effectiveness and advantages of these novel approaches, we can enhance treatment accessibility and elevate the quality of care for those affected by urinary incontinence, ultimately improving their daily functioning and overall well-being. Abbreviated description of the state of knowledge:Current research on innovative treatments for urinary incontinence indicates significant advancements in enhancing patients' quality of life. These cutting-edge methods encompass behavioral therapies like pelvic floor muscle training, state-of-the-art medical technologies such as nerve stimulation, new pharmacological treatments with high efficacy and minimal side effects, and advanced surgical interventions, including artificial sphincter implants and urinary tract modifications. Conclusions: Urinary incontinence is a prevalent health issue that significantly deteriorates the quality of life, particularly affecting half of women and one-third of men over the age of 80. As our society ages and the number of individuals affected by this condition rises, understanding and advancing treatment methods become increasingly crucial. Ongoing research aims to discover new and improved therapeutic approaches with minimal side effects, offering hope for enhanced patient outcomes and better management of urinary incontinence in the future.